The importance of salivary cortisol in the diagnosis of adrenal insufficiency in cirrhosis - Araz, Filiz; Soydaş, Barış; Özer, Birol; Serin, Ender (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Reports on adrenal insufficiency (AI) are unexpectedly high in cirrhosis, and the diagnosis of this condition remains a challenge. We aimed to define the prevalence rate of AI in stable cirrhotic patients and determine the correlations of free cortisol and salivary cortisol with total cortisol. Materials and Methods: Between January 2011 and September 2011, 110 consecutive cirrhotic patients without any infection or hemodynamic instability were enrolled. Baseline total and salivary cortisol levels were measured. The free cortisol level was calculated according to the Coolens’ formula. Post-stimulation total and salivary cortisol levels were measured, and the free cortisol level was recalculated. Results: The mean age of the patients was 62.1±11.4 years. There were 54 males (49.1%). The mean Child-Turcotte-Pugh (CTP) score was 7.2±2.3. Twenty-two (20%) patients were at the CTP-C level. AI was present in 23 (20.9%) and 17 (15.5%) of all patients according to the total and free cortisol criteria, respectively. For basal and stimulated levels, salivary cortisol rather than total cortisol correlates well with free cortisol. Conclusion: The diagnosis of AI on the basis of total cortisol measurement overestimates the prevalence of AI in cirrhosis. Salivary cortisol, which correlates well with free cortisol, is a promising alternative for the diagnosis of AI in cirrhotic patients.